Karakteristik dan Aplikasi Selulosa Kulit Jagung Pada Pengembangan Hidrogel - Lucky Wahyu Nuzulia Setyaningsih; Tintin Mutiara; Clara Yusticia Hapsari; Nabila Kusumaningtyas; Haris Munandar; Romy Jefry Pranata (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2020)
Corn is one of the staple food crops widely consumed by Indonesians, thus has potensial in producing an abundant amount of corn husk waste. Cellulose contained in corn husk is about 44%, so the material has the potential to be source of natural fiber cellulose. The development of hydrogels from natural polymers such as cellulose is very promising especially for biomaterial application. Cellulose fiber was obtained through several stages: dewaxing, pulping, delignification, bleaching and cellulose purification. This study aimed to determine the most effective solvent in cellulose extraction of corn husk, the research carried out with different solvent such as, hydrogen peroxide (H2O2), sodium hypochlorite (NaOCl) and hydrocloric acid (HCl). Based on the functional group formed on the analysis of FTIR, shows that the extraction method using H2O2 as solvent can remove hemicellulose and lignin from the cellulose structure and the most white cellulose fiber obtained from the extraction with H2O2 solvent. Cellulose obtained from previous step was used for hydrogel production. The hydrogel showed different absorption capacity depend on temperature and ratio of glutaraldehide to cellulose. The highest water absorption capacity of 250% obtained by hidrogel with ratio 1:2 at 25oC.